The influence of a patient counseling training session on pharmacy students’ self-perceived communication skills, confidence levels, and attitudes about communication skills training - Jin, Hye Kyung (BMC Med Educ, 2019)
BACKGROUND: The ability to communicate effectively is an essential skill for a pharmacist. However, the curricula of most pharmacy schools in South Korea do not include communication skills training (CST). This study aims to evaluate the effects of CST in pharmacy education. METHODS: This study was a comparison of pre- and post-intervention surveys completed by sixty fifth-year pharmacy students who participated in communication skills and patient counseling training during the spring 2017 semester. The students were asked to respond to 49 questions addressing 4 self-assessment categories: communication skills (24), attitudes (19), and confidence levels (2) at the beginning and end of the CST, and their perception of CST (4) after completing the course. The training session included lectures, small group work, role play, videos, and performance feedback by a tutor. Data were analyzed using the paired t-test with Bonferroni’s correction for multiple comparisons. The open-ended questions were analyzed using inductive content analysis. RESULTS: The pharmacy students’ self-assessment of their communication skills, attitudes toward the communication course, and confidence levels showed significant improvement after the CST. Most students (96.7%) indicated the necessity of a pharmacy communication curriculum. They responded that CST is helpful for effective communication with patients (33.3%) and other healthcare professionals (31.7%). Role-playing was reported as the most preferred learning method (58.3%). CONCLUSIONS: CST significantly impacted pharmacy students’ skills, attitudes, and confidence levels related to communication skills and patient counseling. These findings indicate that communications training should be included in the regular curriculum of pharmacy schools.